Having Multiple Sexual Partners among Iranian Intra-Venous Drug Users - Assari, Shervin; Yarmohamadivasel, Mosaieb; Moghani Lankarani, Maryam; Sehat, Mahmood; Narenjiha, Hooman; Rafiey, Hassan; Noori, Roya; Shirinbayan, Peymaneh; Ahmadi, Khodabakhsh (Frontiers in Psychiatry, 2014)
Background: Transmission of HIV from intra-venous drug users (IDUs) to the community occurs predominantly through high-risk sexual behaviors. Limited information exists regarding the high-risk sexual behaviors of IDUs in Iran. Aim. The aim of this study was to determine the prevalence and factors associated with having multiple sexual partners among Iranian IDUs. Methods. This is a national survey on drug-dependent adults. Participants were sampled from medical centers, prisons, and streets of capitals of 29 provinces in Iran, between May 2007 and February 2008. We analyzed data of 1,416 current IDUs. Socio-demographics and drug use characteristics were entered into a binary logistic regression model to determine predictors of having multiple sexual partners. Results. Having multiple sexual partners in the past or at the time of survey was reported by 56.4% of Iranian IDUs. Multivariate analysis showed that the likelihood of having multiple sexual partners in IDUs decreased by being married (odds ratio [OR], 0.38; P < .001) and increased by female gender (OR, 13.44; P = .02), having illegal income (OR, 1.72; P = .003), higher monthly family income (OR, 1.01; P = .003), pleasure, curiosity, and recreation as cause of first drug use (OR, 1.37; P = .04), ruins as usual place for injection (OR, 1.89; P = .001), and history of syringe sharing (OR, 1.50; P = .02). Conclusions. Having multiple sexual partners was reported by majority of Iranian IDUs, and this was linked to socio-demographics, initiation data, and other risk behaviors. This information should be considered in prevention efforts to reduce sexual transmission of HIV infection in Iran.